2009
DOI: 10.1007/s11356-009-0133-5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of HCH isomers in open soil and plant-rhizospheric soil system of a contaminated environment

Abstract: Recently, alpha-, beta- and gamma-HCH have been nominated by the POPs Reviewing Committee for inclusion into the Stockholm Convention to address the HCH contamination on a global level. Therefore, there is an urgent need to stop the production of lindane and remediate contaminated soil sites. Based on the monitoring studies, the promising species like W. somnifera and S. torvum may be selected for the on-site phytoremediation of HCH-contaminated soil. The mismanagement of HCH residues from the organochlorine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 51 publications
0
7
1
Order By: Relevance
“…The isomer pattern found in soil and water around the production site in the present study was found to be significantly different from the pattern reported by Abhilash et al (2008) and Abhilash and Singh (2009) in their phytoremediation study conducted in another field close to lindane production unit. In all soil sample analyses reported by these workers and which were taken from a single area, β-HCH was the dominant isomer present together with significant concentrations of γ-HCH.…”
Section: Contamination and Run-off From The Production Areacontrasting
confidence: 99%
See 2 more Smart Citations
“…The isomer pattern found in soil and water around the production site in the present study was found to be significantly different from the pattern reported by Abhilash et al (2008) and Abhilash and Singh (2009) in their phytoremediation study conducted in another field close to lindane production unit. In all soil sample analyses reported by these workers and which were taken from a single area, β-HCH was the dominant isomer present together with significant concentrations of γ-HCH.…”
Section: Contamination and Run-off From The Production Areacontrasting
confidence: 99%
“…Overall, Σ HCH levels were reduced to <30% of the original levels in 24 days and to less than 3% in 240 days using ex situ biostimulation techniques. In other studies by Abhilash and Singh (2009) results indicating phytoremediation activity at a site contaminated by HCH close to the factory has been reported. While bioremediation or phytoremediation approaches may have potential in addressing HCH contaminated sites it will be necessary to understand fully the limitations of such approaches.…”
Section: Preliminary Studies On Degradation and Remediation Of Hch Comentioning
confidence: 79%
See 1 more Smart Citation
“…As many other persistent organic pollutants (POPs), β-HCH is resistant to natural degradation, persists for several years in soils and sediments (Calvelo Pereira et al, 2006;Waliszewski et al, 2008;Abhilash and Singh, 2009) and accumulates in vegetables and animal tissues. Mammal intake of β-HCH occurs mainly through the diet and the contaminant is excreted with milk (Hanaoka et al, 2002;Lee et al, 2007;McGraw and Waller, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…4 Although the use of technical HCH was discontinued in these countries and regions over 10 years ago, the environmental levels of HCH isomers were still high, 5,6 and posed a significant impact on ecosystems. 7 Presently, β-HCH is the predominant isomer in the environment 8 and human body 7 because of its resistance to microbial degradation and strong potential to bioaccumulate. 9 Like other POPs, partitioning and exchange of β-HCH among environmental matrices are strongly affected by temperature.…”
Section: ■ Introductionmentioning
confidence: 99%